The Influence Of Orthodontic Treatment On Dental Pulp Response To Sensitivity Tests - Vlad, Ramona; Panainte, Irinel; Hantoiu, Liana; Monea, Monica (European Scientific Journal, ESJ, 2016)
Aim of our study. To evaluate the difference between sensory detection threshold reactions of teeth under orthodontic treatment with fixed appliances, determined by electrical and thermal pulp testing. Material and methods. After a selection based on inclusion and exclusion criteria, 51 patients with a mean age of 19,3+/- 3,6 years old who presented to the Center for Integrated Dental Medicine of the Faculty of Dental Medicine from Târgu Mureș for orthodontic treatment had been included in this study. The reactions to thermal and electrical pulp testing were measured at baseline, after 8 weeks of treatment and during the contention period. Results. The application of orthodontic force immediately increased the response threshold which peaked after 8 weeks. Conclusions. Based on these results we conclude that dental specialists should interpret with caution the results of electric pulp testing in teeth under orthodontic treatment with fixed appliances as the cold tests with ethyl chloride are more reliable.